Exegetical and Theological Implications of ίερόν and ναός in Mark 11-15 - Mikołajczak, Mieczysław (Analecta Cracoviensia, 2011)
The analysis undertaken by the author of this article aims at the presentation of mutual exegetical - theological implications of the usage of ίερόν and ναός in Mk 11-15. The objective of the research carried out in this article is to find an answer to the following question: Has the theme of the temple during the Passion of Christ been presented by Marc from a new perspective and if so then to what extent. The problem whether the usage respectively of ίερόν and ναός is just a reference to the setting has also been taken into consideration. In his research the author has come to a conclusion that the theme of ίερόν and ναός in Mk 11-15 has not been presented by Marc as the essential part of the chapters in question. But at the same time the theme of the temple in the second Gospel helps the reader to notice and to understand the role and significance of the Messiah, the Son of God. That is why St. Marc has not abandoned the theme of the temple in his description of the Passion of Christ but continues it discreetly until he comes to the heart of it which is also the heart of the Gospel - the cross. The author comes to a conclusion that in Mk 11-15 there is a distinct and contrasting difference between ίερόν and ναός but simultaneously each term used by the evangelist in its proper context renders the meaning and sense in a very precise way, just as the context of the Gospel narrative would require. St. Marc does it in a very coherent and conscientious way - much better than other evangelists or classical Hellenic authors do.